Synthesis of activated carbon from biowaste of fir bark for methylene blue removal. Issue 9 (11th September 2019) - Luo, Lu; Wu, Xi; Li, Zeliang; Zhou, Yalan; Chen, Tingting; Fan, Mizi; Zhao, Weigang
Abstract : Activated carbon (AC) was successfully prepared from low-cost forestry fir bark (FB) waste using KOH activation method. Morphology and texture properties of ACFB were studied by scanning and high-resolution transmission electron microscopies (SEM and HRTEM), respectively. The resulting fir bark-based activated carbon (ACFB) demonstrated high surface area (1552 m 2 g −1 ) and pore volume (0.84 cm 3 g −1 ), both of which reflect excellent potential adsorption properties of ACFB towards methylene blue (MB). The effect of various factors, such as pH, initial concentration, adsorbent content as well as adsorption duration, was studied individually. Adsorption isotherms of MB were fitted using all three nonlinear models (Freundlich, Langmuir and Tempkin). The best fitting of MB adsorption results was obtained using Freundlich and Temkin. Experimental results showed that kinetics of MB adsorption by our ACFB adsorbent followed pseudo-second-order model. The maximum adsorption capacity obtained was 330 mg g −1, which indicated that FB is an excellent raw material for low-cost production of AC suitable for cationic dye removal.